2022
DOI: 10.1108/caer-01-2022-0011
|View full text |Cite
|
Sign up to set email alerts
|

Coalitions in international relations and coordination of agricultural trade policies

Abstract: PurposeThe author attempts to examine the existence and pattern of coalitions in international relations across countries, and investigates whether international relations of coalition partners influence a country's enaction of agricultural non-tariff measures (NTMs).Design/methodology/approachThe author adopts a machine learning technique to identify international relation coalition partnerships and use network analysis to characterize the clustering pattern of coalitions with high-frequent records of global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…The author then constructed a monthly dataset of agricultural non-tariff measures (NTMs) against China and international relations with China of each importer and its coalition partners and estimated impulse response functions of agricultural NTMs with regard to international relation shocks. Mao (2023) also identified two major clusters of coalitions, one composed of coalitions primarily among “North” countries and the other of coalitions among “South” countries. The USA is found to play a pivotal role by connecting the two clusters.…”
Section: Machine Learning and Its Application In Agricultural Economicsmentioning
confidence: 95%
See 1 more Smart Citation
“…The author then constructed a monthly dataset of agricultural non-tariff measures (NTMs) against China and international relations with China of each importer and its coalition partners and estimated impulse response functions of agricultural NTMs with regard to international relation shocks. Mao (2023) also identified two major clusters of coalitions, one composed of coalitions primarily among “North” countries and the other of coalitions among “South” countries. The USA is found to play a pivotal role by connecting the two clusters.…”
Section: Machine Learning and Its Application In Agricultural Economicsmentioning
confidence: 95%
“…In this special section, Mao (2022) used the LASSO algorithm to identify international relation coalition partnerships and used network analysis to characterize the clustering pattern of coalitions with high-frequency records of global event data. The author then constructed a monthly dataset of agricultural non-tariff measures (NTMs) against China and international relations with China of each importer and its coalition partners and estimated impulse response functions of agricultural NTMs with regard to international relation shocks.…”
Section: Machine Learning and Its Application In Agricultural Economicsmentioning
confidence: 99%
“…Sun D X and Cheng S T determined that agricultural green technology innovation is the key factor to realize carbon emission reduction [39], Chen F F found that, at present, China has low transformation rate of green technology innovation achievements, and the effect of green energy saving and emission reduction in agriculture is highly difficult to achieve [40]. Mao S P and Yang Y L classified and quantified the agricultural scientific and technological innovation policies issued at the national level since the reform and opening up (1978-2015) from three dimensions, and quantitatively explored its evolution trend and characteristics [41]. Based on the previous research on the progress of agricultural science and technology and green agriculture, this study plans to further deepen the logical relationship.…”
Section: Literature Reviewmentioning
confidence: 99%